Structural characterization and immunomodulatory activity of a water-soluble polysaccharide from Ganoderma leucocontextum fruiting bodies. (1st December 2020) - Gao, Xiong; Qi, Jiayi; Ho, Chi-Tang; Li, Bin; Mu, Jingjing; Zhang, Yuting; Hu, Huiping; Mo, Weipeng; Chen, Zhongzheng; Xie, Yizhen
Graphical abstract: Abstract: Ganoderma leucocontextum is a new species of Ganoderma discovered in 2014. Up to now, the structural characteristics and immunoregulatory activity of its polysaccharides remain virtually unknown. In this study, a water-soluble polysaccharide termed, GLP-3, was purified from G. leucocontextum by ultrafiltration and column chromatography. The results revealed that GLP-3 mainly consisted of glucose (92.7 %) and its weight average molecular weight was 159.7 kDa. The structural analysis indicated that the backbone of GLP-3 was →4)- α -D-Glc p -(1→4, 6)- β -D-Glc p -(1→ with a β -Glc p -(1→ branch. Atomic force microscopy and Congo red experiments revealed that GLP-3 might possess a globular structure with triple-helix conformation in water. Moreover, GLP-3 was recognized by toll-like receptor 2 (TLR2) and exerted immunomodulatory effects via activating mitogen-activated protein kinases (MAPKs), phosphatidylinositol-3-kinase (PI3K)/Akt and nuclear factor- κ B (NF- κ B) signaling pathways in RAW 264.7 macrophages. Collectively, these results suggested that GLP-3 could be developed as a potential functional food ingredient for immunomodulation.